Analysis of the Relationship Between Library Services and Education Factors on the Community Literacy Development Index Using Path Analysis - Benaya; Marga, Diva Aura; Banisa, Rizkia Syefira; Yuniar; Loves, Luvita (Magister Program of Mathematics, Universitas Lampung, 2024)
The application of Path Analysis for causal modelling is widely used in various fields of study, one of which is education. Path Analysis is applied to test the relationship model between variables: CLDI (Community Literacy Development Index) (Y0), library service equity (X1), library collection adequacy (X2), library staff adequacy ratio (X3), community visit rate per day (X4), and education completion rate (X5). In addition, the adequacy of the library collection (X2), the level of community visits (X4), and the level of education completion (X5) significantly affect the CLDI (Y0). The combination of library and education service variables explained 70.19 per cent of the variation in CLDI. This study concludes the importance of synergy between libraries and education in improving community literacy and recommends strengthening literacy programmes based on library services and quality education.